PRELIMINARY CLINICAL RESULTS WITH LIPOASPIRATE STROMAL VASCULAR CELL FRACTION IN TREATMENT OF PATIENTS WITH KNEE OSTEOARTHRITIS - E. Ya. Shevela; N. A. Nitsa; N. M. Starostina; S. I. Baranov; Yu. A. Kozhevnikov; N. D. Popova; E. V. Batorov; A. A. Ostanin; E. R. Chernykh (Медицинская иммунология, 2017)
The paper presents results of clinical application of autologous stromal-vascular fraction (SVF) cells in patients with degenerative osteoarthritis (OA) of the knee, grade II and III (Kellgren–Lawrence scale).We recruited six patients with knee OA (3 men and 3 women; median age 64 years) with mean disease duration of 7 years. All the patients were administered a single intra-articular injection of autologous nucleated SVF cells at an average dose of 16.8±0.9 × 106 per joint (a total of 11 joints). The patients did not experience any serious side effects (allergic, toxic or inflammatory) related to the knee injection. Patient surveys at 1 month after SVF administration revealed a decrease in the severity of pain, as measured by a visual analog scale (VAS) and a specialized 100-point scale KOOS (subscale "pain") (p < 0.05 on both scales). Moreover, the patients reported improvement in the joint functions and quality of life related to affected joints on a KOOS scale (p < 0.05). These positive clinical changes persisted during 6 month follow up. Significant improvements were noted in ultrasound findings, with increased thickness of the cartilage layer at 3 months (in 73% of cases) and at 6 months (in 82%). Our pilot study demonstrated the safety and tolerability of intra-articular injection of autologous SVF cells in patients with moderate to severe OA. The results obtained also indicate a significant antiinflammatory effect of autologous adipose tissue SVF cells, which is manifested at the early stages of cell therapy. Our further investigations will be focused on exploring the SVF stimulatory effects on regeneration of damaged joints.